Factors associated with acute kidney injury among preterm infants administered vancomycin: a retrospective cohort study - Baek Sup Shin; Seung Han Shin; Seul Gi Park; Ee-Kyung Kim; Han-Suk Kim (BMC, 2023)
Abstract Background Vancomycin (VCM) is a widely used antibiotic for the treatment of gram-positive microorganisms, with some nephrotoxic effects. Recent studies have suggested that piperacillin-tazobactam (TZP) aggravates VCM-induced nephrotoxicity in adults and adolescents. However, there is a lack of research investigating these effects in the newborn population. Therefore, this study investigates whether the concomitant use of TZP with VCM use increases the risk of acute kidney injury (AKI) and to explore the factors associated with AKI in preterm infants treated with VCM. Methods This retrospective study included preterm infants with birth weight < 1,500 g in a single tertiary center who were born between 2018 and 2021 and received VCM for a minimum of 3 days. AKI was defined as an increase in serum creatinine (SCr) of at least 0.3 mg/dL and an increase in SCr of at least 1.5 times baseline during and up to 1 week after discontinuation of VCM. The study population was categorized as those with or without concomitant use of TZP. Data on perinatal and postnatal factors associated with AKI were collected and analyzed. Results Of the 70 infants, 17 died before 7 postnatal days or antecedent AKI and were excluded, while among the remaining participants, 25 received VCM with TZP (VCM + TZP) and 28 VCM without TZP (VCM-TZP). Gestational age (GA) at birth (26.4 ± 2.8 weeks vs. 26.5 ± 2.6 weeks, p = 0.859) and birthweight (750.4 ± 232.2 g vs. 838.1 ± 268.7 g, p = 0.212) were comparable between the two groups. There were no significant differences in the incidence of AKI between groups. Multivariate analysis showed that GA (adjusted OR: 0.58, 95% CI: 0.35-0.98, p = 0.042), patent ductus arteriosus (PDA) (adjusted OR: 5.23, 95% CI: 0.67-41.05, p = 0.115), and necrotizing enterocolitis (NEC) (adjusted OR: 37.65, 95% CI: 3.08-459.96, p = 0.005) were associated with AKI in the study population. Conclusions In very low birthweight infants, concomitant use of TZP did not increase the risk of AKI during VCM administration. Instead, a lower GA, and NEC were associated with AKI in this population.